ANALISIS DAMPAK PEMBELAJARAN BERBASIS HUMANISTIK TERHADAP PERKEMBANGAN KEPRIBADIAN POSITIF PESERTA DIDIK SEKOLAH DASAR - Sri Wahyuni; Jurianto (Universitas Negeri Medan, 2026)
Elementary school is a crucial stage for shaping students’ character and personality. However, learning practices in schools are still predominantly teacher-centered and focused on cognitive achievement, resulting in less optimal character development. This study aims to analyze the implementation of a humanistic learning approach and its implications for the development of positive character among elementary school students. This research employed a descriptive qualitative approach involving teachers, students, and the school principal as research participants, selected through purposive sampling. Data were collected through interviews, classroom observations, and document analysis, and analyzed using an interactive data analysis model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of humanistic learning is reflected in student-centered learning practices, the teacher’s role as a facilitator, and the creation of a safe, comfortable, and inclusive learning environment. The humanistic approach contributes positively to students’ personality development at SDN Sukorejo II, including increased self-confidence, responsibility, empathy, creativity, and collaboration skills. Therefore, humanistic learning is considered effective in supporting the holistic development of elementary school students, encompassing cognitive, affective, and social dimensions.